In vitro Cytotoxicity, Apoptotic and Hemolysis Assay of Kalsilite‐Based Glass Ceramics for Dental Veneering Application. Issue 1 (14th July 2015) - Kumar, Pattem; Singh, Vinay; Hira, Sumit; Manna, Partha; Kumar, Pradeep
Abstract : Nanocrystalline kalsilite material was synthesized via a gel‐trapped coprecipitation for dental veneering applications. The prepared kalsilite powder was further mixed with a separately processed low temperature frit (LTF), in different weight ratio to optimize its coefficient of thermal expansion (CTE). These mixes were analyzed for their flexural strength and surface morphology. The cytocompatibility of mixes was investigated with reference to their effect on human buccal epithelial cells (SCC‐25). The flexural strength and CTE values of prepared kalsilite have been found to be comparable to the values obtained for a commercial opaque VMK 95 1M2 (product no. B333250; VITA Zahnfabrik H. Rauter GmbH KG Postfach 1338 D‐79704 Bad Sackingen, Germany). This confirmed the feasibility of prepared kalsilite material for dental veneering application. Kalsilite glass‐ceramic materials caused moderate levels of apoptosis in SCC‐25 cells at higher concentrations and were also tolerable by human RBC as evaluated from hemolytic assay. Human buccal epithelial cells were tolerant to kalsilite glass‐ceramic materials at lower concentrations although higher concentration (500 μg/mL) caused moderate damages in proliferative capacity of SCC‐25. The improved mechanical and biological properties of the prepared kalsilite confirmed its potential use in dental veneering.